Genome-Wide Analysis of the AP2/ERF Superfamily Genes and their Responses to Abiotic Stress in Medicago truncatula - Shu, Yongjun; Liu, Ying; Zhang, Jun; Song, Lili; Guo, Changhong (Frontiers in Plant Science, 2016)
The AP2/ERF superfamily is a large, plant-specific transcription factor family that is involved in many important processes, including plant growth, development, and stress responses. Using Medicago truncatula genome information, we identified and characterized 123 putative AP2/ERF genes, which were named as MtERF1–123. These genes were classified into four families based on phylogenetic analysis, which is consistent with the results of other plant species. MtERF genes are distributed throughout all chromosomes but are clustered on various chromosomes due to genomic tandem and segmental duplication. Using transcriptome, high-throughput sequencing data, and qRT-PCR analysis, we assessed the expression patterns of the MtERF genes in tissues during development and under abiotic stresses. In total, 87 MtERF genes were expressed in plant tissues, most of which were expressed in specific tissues during development or under specific abiotic stress treatments. These results support the notion that MtERF genes are involved in developmental regulation and environmental responses in M. truncatula. Furthermore, a cluster of DREB subfamily members on chromosome 6 was induced by both cold and freezing stress, representing a positive gene regulatory response under low temperature stress, which suggests that these genes might contribute to freezing tolerance to M. truncatula. In summary, our genome-wide characterization, evolutionary analysis, and expression pattern analysis of MtERF genes in M. truncatula provides valuable information for characterizing the molecular functions of these genes and utilizing them to improve stress tolerance in plants.